Contemporary Asian Popular Culture Vol. 1
XXXI, 292 p. 66 illus., 59 illus. in color.
Keywords: “The current two volumes are the most comprehensive and authoritative academic publications on Asian popular culture. They aptly document the ways in which Squid Game plays a pivotal role in shifting cultural production, and how the Korean Wave around the globe keeps going strong, both practically and academically. The readers of the books will be able to utilize cutting-edge debates and empirical studies guided by some of the finest scholars in the field.” —Dal Yong Jin, Simon Fraser University, Canada “Squid Game is a game-changer, and this essential two-volume collection pays tribute to the power of Asian popular media to speak to audiences far beyond the region about the precarious lives we share in the second decade of the twentyfirst century.” —Gina Marchetti, Pratt Institute, New York, USA “Contemporary Asian Popular Culture is essential for anyone seeking to understand the profound influence and intricate narratives of contemporary Asian popular media. Together, these volumes provide a crucial resource for scholars, students, and enthusiasts alike.” —Eunyoung Kim, Auburn University at Montgomery, USA This volume explores how contemporary Asian popular culture reflects on and critiques social issues. The authors explore how shows like Squid Game present a scathing critique of oppressive socio economic structures, conceptualize national heterotopias, utopias, and dystopias, and facilitate understanding of identity formation and discourses of resistance. Yeojin Kim is an associate professor in Communication at Central Connecticut State University, USA. Dharshani Lakmali Jayasinghe is an assistant professor of Anglophone and World Literatures in the Department of English at Central Connecticut State University, USA. Hiba Aleem is an adjunct faculty member in the Department of English, Writing, and Communication at Emmanuel College in Boston, USA. Karen A. Ritzenhoff is a professor in Communication and Women, Gender, and Sexuality Studies at Central Connecticut State University, USA.